178k views
0 votes
What is the remainder when (3x4 + 2x3 − x2 + 2x − 9) ÷ (x + 2)?

2 Answers

4 votes

Answer:

15

There you go.

User Spoeken
by
6.1k points
4 votes
ANSWER

The remainder is 15.



Step-by-step explanation

The given polynomial function is


p(x) = 3 {x}^(4) + 2 {x}^(3) - {x}^(2) + 2x - 9

We want to find the remainder when the given polynomial function is divided by


x + 2



According to the Remainder Theorem, if


p(x) = 3 {x}^(4) + 2 {x}^(3) - {x}^(2) + 2x - 9

is divided by


x + 2


Then the remainder is


p( - 2)


This means that, we have to substitute


x = - 2
into the given polynomial function and evaluate.


Thus,


p( - 2) = 3 {( - 2)}^(4) + 2 {( - 2)}^(3) - {( - 2)}^(2) + 2( - 2)- 9




p( - 2) = 3 {( 16)} + 2 {( - 8)} - {( 4)} + 2( - 2)- 9



p( - 2) = 48 - 16- 4 - 4- 9



p( - 2) = 15

Therefore the remainder is 15
User Thientvse
by
5.8k points